A bio-inspired methodology of automatic perching for unmanned aerial vehicles - Chi, Wanchao (2016)
Current unmanned aerial vehicles (UAVs) have to stay airborne during surveillance missions, decreasing their energy efficiency dramatically and therefore limiting their endurance significantly. On the other hand, birds perch to conserve energy while maintaining surveillance over their domain. A biomimetic methodology of automatic perching for UAVs is thus a promising solution to their endurance problem.